Citrus fruits through looking glass - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Interested in the potential of citrus fruits? The Active Citrus Germplasm bank at the Sylvio Moreira Centre, in Cordeiropolis (Brazil) is one of the world s leading citrus centres, covering 1,800 varieties. The Bank is first and foremost a...